Similarities and Differences in Consumer Orientation and Marketing Strategies among Malay Men and Women Entrepreneurs in Malaysia - Yacob, Nik Rahimah Nik (Accounting Department,, 1996)
Does entrepreneur’s gender influence his or her consumer orientation and marketing strategies? Based on the role-centered perspective, this paper posited that man and women entrepreneurs would not differ in their consumer orientation and in their evaluation of some generic marketing strategies. However, the empirical results from a small sample of Malay men and women entrepreneurs in peninsula Malaysiaindicate an insignificant gender influence on consumer orientation. But contrary to expectations, the results for tow marketing strategies indicate a significant gander influence. Some possible explanations for the contradictory findings are also discussed.